La neuroeducación y el trastorno personal antisocial (TPA) - Parra Reyes, David (2016)
The current Peruvian education is experiencing very critical moments since the learning process looks simplified to the simple memorization or mechanization of concepts and/or data processing which do not contribute to significant learning and that is rather influencing on the educational disinterest for the students. Reason why the present article aims to awaken the interest of responsible people for the education of learners and that through the knowledge of brain functions can be developed the necessary tools that contribute to develop the capacities that must be for the achievement of expected learning.Current studies in neuroeducation have shown that many students have developed personal antisocial  disorders because of several factors that have contributed to the emergence of these, which at the same time are generating much violence and juvenile crime.